Using the board game Borel to illustrate probability calculation. (1st July 2019) - Johnson, Roger W.
Summary: The Borel board game consists of a series of experiments involving dice rolls, coin flips, or drawing colored balls from bags. Before each experiment is conducted, each player bets for or bets against a statement regarding the random outcome. We suggest that the collection of Borel experiments be used as a resource to illustrate probability calculation.